Microwave Signal Generation in Single-Layer Nano-Contact Spin Torque Oscillators - Sani, Sohrab Redjai; Durrenfeld, Philipp; Mohseni, Seyed Majid; Chung, Sunjae; Akerman, Johan (IEEE transactions on magnetics, 2013)
We demonstrate spin transfer torque (STT) driven microwave signal generation, from about 250 MHz to above 3 GHz, in single permalloy layers underneath a nano-contact with diameter of 100 nm. The threshold current for signal generation is found to be strongly hysteretic, the microwave signal shows a number of harmonics, zero-field operation is straightforward, and the microwave frequency increases quasi-linearly with drive current. All observations are consistent with STT driven motion of a vortex-antivortex pair nucleated by the Oersted field underneath the nano-contact. While the generated power is about 10 dB smaller than the best GMR based nanocontact spin torque oscillators, the linewidth of 6-100 MHz is of the same order.